Pengaruh Kualitas Produk, Harga, Promosi dan Tempat Pendistibusian Terhadap Keputusan Pembelian Sepeda Motor Yamaha Pada Perusahaan Tjahaja Baru Bukittinggi - Hariman Syaleh (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2017)
Yamaha as a growing automotive company today realizes the importance of strategy in winning market competition.This research aims to determine the effect of product quality, price, promotion and istribution place on purchasing decision of yamaha motorcycle in Tjahaja Baru Bukittinggi. Sample of this research are 96 customers who buy Yamaha motorcycle in company Tjahaja Baru Bukittinggi which is chosen by accidental sampling technique.Variablesused in this research are of Product X1, Price X2, Promotion X3 and Distribution X4 as independent variable and purchase decision as dependent variable. Data analysis technique used is multiple linear regression.The result of this study indicate that the product, promotion and distribution have a positive and significant effect on purchasing decision of Yamaha motor in company Tjahaja Baru Bukittinggi, while price has a positive but not significant effect on purchasing decision of Yamaha motor in company New Tjahaja Bukittinggi. Keywords: Products, Price, Promotion, Distribution, Buying decision